MOTIF DAN PERAN PEREMPUAN DALAM BEKERJA TERHADAP KINERJA DI THE GRAND PALACE HOTEL MALANG - Avrilia Deby Angrila Sari; Hadi Sunaryo (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study is intended to determine the motives and roles of women in working towards performance. The population of this study was a female company at The Grand Palace Hotel Malang with a sample of 32 people, and a sample called a census sample. This research uses quantitative descriptive method, analysis in this method uses tabulation data. In the analysis, considering cultural, economic and educational motives greatly influences women in the company. Motives provide encouragement for women in the world of work specifically for employees of The Grand Palace Hotel, with the motive will provide encouragement for women who have good performance at work. Not only to make a living but also to improve their profession. In the role of the world of work, women will have several roles, namely productive roles, domestic roles, and social roles. The role includes the role of women in the world of work and women who act as housewives. Having this role is not an easy thing, but because it has a motive that supports women who have good performance at work and can manage the household well.Keywords: motives, women's roles, performance